The Effect of Birthing Ball Use on the Duration of the First Stage of Active Labor - Dewi Fika Abubakar; Rani Safitri; Rosyidah Alfitri (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Birth and delivery are normal physiological events involving the expulsion of the fetus that occurs during 37-42 weeks (full term pregnancy). For a mother, the labor process can cause fear and pain so that the risk of labor that is too long increases. By using a birthing ball, the mother can move more comfortably and experience less pain, so that labor will be shorter. This study aims to determine the Effect of Using a Birthing Ball on the Length of Stage 1 of the Active Phase at the Paguyaman Gorontalo Health Center. The purpose of this study was to analyze how the birthing ball method affects the length of the active phase I stage. The design of this study was a static Group Comparison pre-experimental design. Statistical tests with the Independent T Test. The population of this study were mothers giving birth at the Paguyaman Gorontalo Health Center. The sample consisted of 32 people. The results of the study on the use of birthing balls obtained an average labor progress of 288 minutes. The results of the statistical test with a significance value of 0.00 which means p <0.05. The conclusion of this study is that there is a significant influence in the use of the birthing ball method on the length of the first active phase in mothers giving birth in the Paguyaman Gorontalo Health Center Area. Suggestions for health workers in making plans to improve maternal care during labor by using birthing balls to help the progress of labor.